An Integrated Management System to reduce False Codling Moth, Thaumatotibia leucotreta (Meyrick) (Lepidoptera: Tortricidae) infested citrus fruit from being packed for export - Mac Aleer, Clint (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2019)
False codling moth (FCM), Thaumatotibia leucotreta (Meyrick) (Lepidoptera: Tortricidae) is indigenous to southern Africa and is an important pest of citrus in this region. As a result of its endemism to sub-Saharan Africa, several countries to which South Africa exports citrus, regulate it as a phytosanitary pest. Consequently, it is necessary to ship fruit to these markets under cold-disinfestation protocols. This has been possible, as until recently, all of these markets could be considered relatively small niche markets. The South African citrus industry exports approximately 130 million cartons of fruit (15 kg equivalent) annually. During the 2017 season, a total of 48 million cartons were exported to the European Union (EU), which is the equivalent of 41% of South Africa's total export volume, thus making the EU South Africa's most important export market. In 2013 the European and Mediterranean Plant Protection Organisation (EPPO) conducted a pest risk analysis (PRA) on FCM, leading to the EU declaring it an officially regulated pest for this region, effective of 1 January 2018. Citrus is regarded as a preferred non-native host of FCM and South African citrus was identified as a primary focus due to large volumes being exported to Europe. Shipping under cold disinfestation is not possible with such large volumes of fruit. Additionally, several cultivars would suffer high levels of chilling injury under such conditions. In this study, an Integrated Management System was tested with pre- and postharvest controls to test the hypothesis that pre-harvest interventions resulted in lower post-harvest infection. Thirty orchards ranging from soft citrus cultivars such as Nule and Nova Mandarins, to Navel orange cultivars such as Newhall, Palmer and Late Navel and ending with Valencia cultivars such as Midknight and Delta, were identified for this study. This system relies on pre-harvest inspections such as FCM trap counts and fruit infestation on data trees in every orchard, with associated thresholds for action or continued compliance. Inspections were conducted on a weekly basis. There was a significant relationship between the moth catches and FCM infestation for the full monitoring period, using a two-week lag period for infestation. Inspections of harvested fruit were conducted at the packhouse to determine FCM infestation. This included inspection of the fruit on delivery to the packhouse, on the packing line, and a final fruit sample taken from the packed product and inspected for FCM. The highest levels of infestation were recorded on the Navel cultivars, thus confirming that Navels cultivars are a preferred host for FCM. Significant positive relationships were recorded between FCM infestation during the last 4 weeks before harvest and the level of infestation in the fruit delivered to the packhouse and between the fruit delivered to the packhouse and in the fruit packed in a carton for export. There was a substantial reduction in infestation between the fruit delivered to the packhouse and the fruit packed in a carton for export, with certain orchards recording as much as a 93% reduction in the fruit packed in a carton, which indicated that the packhouse could effectively identify and remove FCM infested fruit. The outcome of the study is that a holistic management approach minimizes the risk of FCM in citrus fruit destined for export and therefore mitigate the risk associated with FCM.
Keywords: Cryptophlebia leucotreta -- South Africa; Cryptophlebia leucotreta -- Biological control -- South Africa; Citrus -- Diseases and pests -- Biological control -- South Africa; Insect pests -- Biological control -- South Africa; Insecticides; Citrus fruit industry -- South Africa; South Africa -- Commerce -- European Economic Community Countries